2005
DOI: 10.1029/2004gl021343
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional finite difference time domain modeling of the Earth‐ionosphere cavity resonances

Abstract: [1] Comparison of results from a three-dimensional (3-D) finite difference time domain (FDTD) model of Schumann resonances (SR) with a set of classical eigenfrequency and quality factor solutions for laterally uniform spherically symmetric Earth-ionosphere cavity and recent SR observations during solar proton events (SPEs) and X-ray bursts demonstrate the potential and applicability of the FDTD technique for studies of realistic SR problems.Citation: Yang, H., and V. P. Pasko (2005), Three-dimensional finite d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 27 publications
(59 reference statements)
6
74
0
5
Order By: Relevance
“…[20] Comparing our FDTD results and data reported by Price and Melnikov [2004], some different features are observed in these two frequency variation patterns (see an example is presented in our previous work [Yang and Pasko, 2005;Yang et al, 2006]. Sentman [1989] found the maximum magnitude of the first mode splitting to be in the range 1.4-1.8 Hz in realistic measurements.…”
Section: Rs2s14supporting
confidence: 50%
See 2 more Smart Citations
“…[20] Comparing our FDTD results and data reported by Price and Melnikov [2004], some different features are observed in these two frequency variation patterns (see an example is presented in our previous work [Yang and Pasko, 2005;Yang et al, 2006]. Sentman [1989] found the maximum magnitude of the first mode splitting to be in the range 1.4-1.8 Hz in realistic measurements.…”
Section: Rs2s14supporting
confidence: 50%
“…Different shifts of the SR parameters were reported in the realistic measurements [e.g., Schlegel and Füllekrug, 1999;Roldugin et al, 2001Roldugin et al, , 2003Roldugin et al, , 2004aSátori et al, 2005]. In our previous work [Yang and Pasko, 2005], the variation patterns of the first SR frequency associated with the ionospheric conductivity perturbation during SPEs and X-ray bursts were discussed. It has been demonstrated that the conductivity perturbation at high altitudes (>70 km) leads to increase in the first SR frequency; whereas, the first SR frequency decreases with the conductivity perturbation at low altitudes (<70 km).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…A simplified version of this model was previously applied to the Earth-ionosphere cavity by Yang and Pasko [2005]. The number of FDTD cells in q and f directions are 20 and 40, respectively.…”
Section: -D Fdtd Modeling For a Planetary Resonant Cavitymentioning
confidence: 99%
“…Nickolaenko et al [1999Nickolaenko et al [ , 2004 and Nickolaenko and Rabinowicz [2001] gave an analytical solution for the ELF pulses from the lighting strokes in the time domain. In our previous work [Yang and Pasko, 2005], a threedimensional (3-D) FDTD model is developed to describe the ELF propagation in the Earth-ionosphere cavity and the variation of SR parameters during solar proton events and X-ray bursts. In this paper, we use this FDTD model to extend our study to other celestial bodies, e.g., Titan, Venus, and Mars.…”
Section: Introductionmentioning
confidence: 99%